Occupational therapy practice used for children diagnosed with a dual diagnosis of cerebral palsy and visual impairment in South Africa - Van Rensburg, Zone Janse (My University, 2016)
Occupational therapy aims to assist children diagnosed with cerebral palsy (CP) to achieve independence in their occupational performance areas. Treatment includes the use of sensory stimulation but when a child’s vision is impaired the use of visual stimulation becomes difficult. Research guiding occupational therapists on how to combine treatment methods successfully when treating children with CP with a co-morbid diagnosis of visual impairment is limited(15)(16). This study aims to determine the occupational therapy practice used, including the therapists’ knowledge; skill and perceived confidence, for children with a dual diagnosis of CP and visual impairment in South Africa. It uses a descriptive, non-experimental, cross-sectional framework within a quantitative research approach. Purposive sampling was used to select participants. This study finds uniformity in the approaches occupational therapists use when managing these children, but these approaches are not always based on best practice. Therapists use clinical expertise and integrate evidence based practice rather than the other way around. This study demonstrates a need for clear protocols on how to manage these children and more accessible postgraduate training in the management of them.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy Johannesburg, 2016
Keywords: Cerebral Palsy; Vision Disorders; Child; Occupational Therapy